The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/icl.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Systemic Omega-3 Fatty Acid Levels With Moderate-to-Severe Dry Eye Disease Signs and Symptoms at Baseline in the Dry Eye Assessment and Management Study

Abstract: fatty acid supplementation is used to treat systemic inflammatory diseases, but the role of n-3 in the pathophysiology and therapy of dry eye disease (DED) is not definitive. We evaluated the relationship of systemic n-3 levels with signs and symptoms at baseline in the Dry Eye Assessment and Management (DREAM) Study. Methods: Blood samples from participants at baseline were analyzed for n-3 and n-6, measured as relative percentage by weight among all fatty acids in erythrocytes. Symptoms were evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…DED etiology and pathology findings have indicated that patients with different DED etiologies may present with different signs and symptoms 8 . It has been reported that patients who smoke or have comorbidities experience more severe symptoms of DED, when compared to patients in a control group 9 . The potential factors that might increase the incidence of DED include primary lacrimal gland diseases, rheumatoid arthritis, ultraviolet ray exposure, improper wearing of contact lenses, older age, female, smoking, and some medicines, such as tricyclic antidepressants and antihypertensive drugs 3,6,[10][11][12] .…”
Section: Background and Summarymentioning
confidence: 99%
“…DED etiology and pathology findings have indicated that patients with different DED etiologies may present with different signs and symptoms 8 . It has been reported that patients who smoke or have comorbidities experience more severe symptoms of DED, when compared to patients in a control group 9 . The potential factors that might increase the incidence of DED include primary lacrimal gland diseases, rheumatoid arthritis, ultraviolet ray exposure, improper wearing of contact lenses, older age, female, smoking, and some medicines, such as tricyclic antidepressants and antihypertensive drugs 3,6,[10][11][12] .…”
Section: Background and Summarymentioning
confidence: 99%
“…Reduced expression of HLA-DR was observed following three month supplementation of omega-3 and -6 [ 140 ]. However, more recent studies have reported no difference between omega-3 and placebo supplement groups on symptoms and signs of DED [ 141 , 142 , 143 ]. Finally, a recent Cochrane review concluded that there is a possible role for long-chain omega-3 supplementation in DED management, although with uncertainty and inconsistency in the evidence [ 144 ].…”
Section: Current Anti-inflammatory Therapies For Dedmentioning
confidence: 99%
“… 65 For instance, the DREAM study concluded that patients with DED who received omega-3 fatty acid supplementation did not show a significant improvement in symptoms compared to a similar cohort that received olive oil as placebo. 66 It is possible, however, that omega-9 fatty acids, which are present in olive oil, could improve DED signs and symptoms similar to omega-3 fatty acids. 67 A meta-analysis of randomized clinical trials of omega-3 fatty acids concluded that they can be effective for treating DED.…”
Section: Introductionmentioning
confidence: 99%